A four-coordinate cobalt(II) single-ion magnet with coercivity and a very high energy barrier - Yvonne Rechkemmer (Nature Portfolio, 2016)
Bistable single-molecule magnets potentially allow information storage at extremely high densities. Here, the authors study an air- and moisture-stable mononuclear tetrahedral cobalt(II) complex, elucidating the origin of its pronounced magnetic bistability.